Sosialisasi Undang-Undang Nomor 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual (UU TPKS) - Agus Santoso; Trie Hierdawati; Siswoyo Siswoyo; Ismail Buhari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Acts of sexual violence are a complex problem and a real threat, both physical and non-physical, that must be prevented and handled seriously, professionally and responsibly. However, the fact is that cases still continue to occur and the resolution of sexual violence cases has not met expectations. Sexual violence in question is non-physical sexual harassment, physical sexual harassment, forced contraception, forced marriage, sexual torture, sexual exploitation and electronic-based sexual violence.